Practical design, construction and operation of food facilities - Clark, J. P., 1942- (Food science and technology (Academic Press), 2009)
Around the world concerns about cost, efficiency, and safety - employee, product, process and consumer - have led to changes in the way food plants are planned, constructed and evaluated. From initiation of major capital requests to legal design requirements to project management and plant operations, food engineers and scientists must understand the myriad of requirements and responsibilities of successful food facilities. J. Peter Clark provides that guidance in this complete volume. Included are: a summary of lessons on understanding how management evaluates potential investments and how they can contribute to ultimate shareholder value, and checklists to help accurately estimate capital and operating costs; important, and in some cases unique, features of a food plant including focus on food safety. It addresses not only consumer products, but ingredients for consumer products and the concerns of distribution and flexibility that must be considered. Also considered are the support facilities that are equally essential to the safe production of food; and, an effective approach to understanding production lines and optimizing operations during expansion by briefly introducing Goldratt's Theory of Constraints. This book explores the challenges of construction while maintaining safe and sanitary operations. It also includes an approach and methodology that can be extended beyond the case studies presented in order to effectively plan development processes and make correct equipment selections. It offers project management and plant operations guidance to assist engineers who find themselves in the role of managing a design or construction process project, or of supervising a portion of a plant. It includes suggestions for effectively troubleshooting an unsatisfactory operation. Key features include: Provides real-world insights including guides for proper project estimation, understanding the role and importance of support facilities, maintaining standards while under construction and other vital considerations; includes checklists and proven approaches to guide the reader through the wide range of necessary planning and implementation steps; and, considers factors for both new plant construction and expansion of existing plants.